Motivation, Self-Efficiency, and Academic Achievement Private Teacher Professional Education Students in Differentiated Learning Courses - Shamdas, Gamar (Journal of Education Reseach and Evaluation, 2023)
Student prospective professional teachers are not enough to equip themselves with scientific content alone but need to balance it with academic motivation and self-efficacy which are useful for the quality of their academic achievements. The aim of this study is to analyze the relationship between academic motivation and self-efficacy with academic achievement. This research is non-experimental research, correlational design with a quantitative approach. The research was conducted with a population of all pre-service PPG totaling 23 students, and all members of the population were sampled. Academic achievement data is the accumulated grades of assignments, midterm, and final semester exams for different learning subjects after 16 meetings. Data on academic motivation and self-efficacy were obtained through a questionnaire. Data on the relationship between academic motivation and self-efficacy with academic achievement were analyzed using multiple linear regression tests. The results of the study show that there is a relationship between academic motivation and self-efficacy with academic achievement. Academic achievement can be predicted with the regression equation y = 76.287 + 0.215x1 + 0.268x2, meaning that an increase in one academic motivation score will increase the academic achievement score by 0.215 (β = 0.433, t(20) = 2.351, p = 0.029), while an increase of one self-efficacy scores will increase academic achievement scores by 0.268 (β = 0.413, t(20) = 2.243, p = 0.036).